CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE DAN KINERJA KEUANGAN PERUSAHAAN - Merdianeu Utami Putri (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to find out how the relationship between corporate social responsibility and good corporate governance with the company's financial performance. The population of this study is state-owned companies listed on the Indonesian stock exchange for the 2016-2019 period. Based on the sampling method, ten companies or business entities became the research sample. To analyze the research data, this study used multiple regression analysis. Then the results of this study obtained that corporate responsibility and good corporate governance have an influence on the financial performance of state-owned enterprises.